Fostering resiliency with good market design: Lessons from Texas - Peter C. Cramton (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2022)
In February 2021, winter storm Uri brought extreme cold to Texas for many days. The cold caused a spike in electricity and natural gas demand and simultaneously a sharp drop in supply. The electricity shortage caused 4.5 million Texans to lose power for multiple days. Many lost water service too. Storm damage was extensive, including many deaths. This paper examines what happened and offers solutions to improve the reliability and resilience of critical infrastructures. Improved communication before and during the storm would limit the damage. Natural gas market reforms would enhance the reliability of the gas supply, enabling more generators to produce power. Improved energy efficiency would limit the cold-induced demand spike. In addition to ongoing initiatives to integrate storage and distributed generation, the system operator should introduce a voluntary forward energy market that lets market participants better manage risk and plan resources to meet demand. Price-responsive demand should also be encouraged to limit demand surges in cold snaps.
Keywords: 330; Infrastruktur; Katastrophe; Krisenmanagement; Coping-Strategie; Texas; USA